THE INFLUENCE OF SUPERVISION, JOB EXPERIENCE, AND PERFORMANCE ON THE CAREER OF THE LECTURER OF INSITUTE ISLAMIC STUDIES HAMZANWADI NAHDLATUL WATHAN PANCOR, EAST LOMBOK - Islahudin, Islahuddin (Journal of Education Research in Administration and Management (JERAM), 2017)
The Objective of this research is to study the direct effect of the supervision, job experience, and performance toward career of the lecture. Research method that been used is quatitative approach with survey method. The techniques of collecting data using questionnaires and interviews. The data analysis was done using descriptive analysis and inferential analysis with the approach of path analysis. The result are : (1)The supervision has positive direct influence on the career, (2) Experience has positive direct influence on the career, (3) Performance has positive direct influence on the career, (4) Supervision has positive direct influence on the performance, (5) Experience has positive direct influence on performance.